Вторичное цветение Silene jailensis N.I. Rubtzov (Caryophyllaceae) — реликтового эндемика Горного Крыма - Никифоров, А.Р. (Український ботанічний журнал, 2009)
Зачатковий генеративний пагін напівкущика Silene jailensis N.I. Rubtzov розвивається у два етапи: розгортання вегетативної частини та формування зачатків генеративних органів. За підвищення температури повітря на початку зими до +10 °С і більше на конусі наростання пагонів дочасно формуються зачатки суцвіття. Створюється друга зимуюча генерація генеративних пагонів. У фазу цвітіння рослини вступають лише після зростання середньодобової температури повітря до +15 °С. Embryonic development of generative shoots of the subshrub Silene jailensis N.I. Rubtzov has two stages: formation of vegetative parts and formation of germinants of generative organs. If the average air temperature increases up to +10 °С and higher at the beginning of winter, sometimes the rudiments of racemes are formed at the ends of shoots before the proper time. In winter and summer the second wintering generation of generative shoots is developed. The plant enters into the blooming (blossom) phase only after the increasing of the average diurnal air temperature up to +15 °С and higher.